Estudio de factibilidad, producción y comercialización del aguacate y sus derivados - Silva C., Vanessa (2009)
The project to carry out consists of Avocado fruit exploitation; fruit which is attributed several properties for prevention some health problems, its rich in vitamin C, vitamin B6, magnesium, and iron. All these components give to our organism improvements immunologic system, bones and teeth, give us stimulus of level physical and mental. The project analysis will take in all supply chain from fruit plantation and harvest to its trading like final product suitable for market consumption. With a part of the production, we get the avocado oil which is originated from whole fruit pulp that crossing through a factory consisting of reception ramps, ripening area, desosarer, amasser, vacuum oil extractor and packer; whose purpose is produce extra virgin oil for human consumption characterizing by its vitamin high contents; and with the rest of the production we carry out the avocado salad manufacture. Inside of the project we will not fall in residue costs, as long as by processing the fruit, the shell will be used like fertilizer for the next harvest and the fruit seed will be the innovator part of this production, we will carry out a natural diuretic. By this motive we have seen the necessity to create these products that will help to the regulation and prevention of the nutritious bad habit with the passage of time has been adopted of the different cultures of our country.